Observational cohort study of the triggers, diagnoses and outcomes of the medical emergency team (MET) response in adult psychiatry inpatients colocated with acute medical services in Australia - Daniel Wirth; Meor Azraai; Jeanette H Pham; Wenye F Looi; Ashley S L Ng; Umesh Babu; Bharat Saluja; Andy K H Lim (BMJ Open)
Objectives Medical emergencies in psychiatric inpatients are challenging due to the model of care and limited medical resources. The study aims were to determine the triggers and outcomes of a medical emergency team (MET) call in psychiatric wards, and the risk factors for MET activation and mortality.Design Retrospective multisite cohort study.Setting Psychiatry units colocated with acute medical services at three major metropolitan hospitals in Melbourne, Australia.Participants We studied 487 adult inpatients who experienced a total of 721 MET calls between January 2015 and January 2020. Patients were relatively young (mean age, 45 years) and had few medical comorbidities, but a high prevalence of smoking, excessive alcohol intake and illicit drug use.Outcome measures We performed a descriptive analysis of the triggers and outcomes (transfer rates, investigations, final diagnosis) of MET calls. We used logistic regression to determine the factors associated with the primary outcome of inpatient mortality, and the secondary outcome of the need for specific medical treatment compared with simple observation.Results The most common MET triggers were a reduced Glasgow Coma Scale, tachycardia and hypotension, and 49% of patients required transfer. The most frequent diagnosis was a drug adverse effect or toxidrome, followed by infection and dehydration. There was a strong association between a leave of absence and MET calls, tachycardia and the final diagnosis of drug adverse effects. Mortality occurred in 3% after MET calls. Several baseline and MET clinical variables were associated with mortality but a model with age (per 10 years, OR 1.61, 95% CI 1.29 to 2.01) and hypoxia (OR 3.59, 95% CI 1.43 to 9.04) independently predicted mortality.Conclusion Vigilance is required in patients returning from day leave, and drug adverse effects remain a challenging problem in psychiatric units. Hypoxic older patients with cardiovascular comorbidity have a higher risk of death.